Subject-Related Ethical Professional Knowledge of Geography Teachers as Prerequisite to Promote Ethical Judgement in Geography Lessons - Laub, Jochen; Felzmann, Dirk; Horn, Michael (Journal of Geography Education, 2021)
Geography education aims at developing students’ capability to make ethical judgements, which requires a critical and reflexive examination of ethical aspects. This paper asks for reasons of the moderate implementation of this objective and focusses on the possible causes that result from teachers’ lack of professional knowledge. Although specialized knowledge is considered to be an important determinant of education quality, it is unclear whether teachers possess these professional skills (the ethical knowledge) needed to deal with this challenge. From the analysis of the moral-psychological construct of moral sensitivity and theoretical approaches to ethics, the authors develop facets of Geography-related ethical professional knowledge.